Faces of religious healing in Nkhoma, Malawi: an exercise in oral history - Landman, Christina (Studia historiae ecclesiasticae, 2018)
On 10 November 2016, the Nkhuni Centre for Oral History was established as part of the Nkhoma Museum at the University of Nkhoma in Malawi. Consequently, the author conducted an oral history project in and around the town of Nkhoma to strengthen the capacity of the centre to engage in future projects. The aim of the research was to record-albeit in restricted numbers-the answers which people living in the villages around Nkhoma, as well as patients in Nkhoma Hospital, gave to the interview questions: "What/who makes you ill?" and "What/who makes you healthy?" Furthermore, the research was to establish the religious ways of healing acknowledged by the interviewees. Finally, the research sought to inform itself on the history-short as it may be-of how and why interviewees have chosen to change from one church to the other, or remain in a specific church, in order to find their preferred way of religious healing. The aim of the article is to present the research results with a focus on the methodological steps taken in doing oral history research.
free
Keywords: Christianity and African religions; Church of Central Africa Presbyterian; Nkhoma Synod.; Healing; Spiritual; Health and religion; Malawi – Religion; Medicine and religion; Oral history